Predictors of Effective Working Memory Training in Individuals with Alcohol Use Disorders. (25th October 2018) - Gunn, Rachel L.; Gerst, Kyle R.; Wiemers, Elizabeth A.; Redick, Thomas S.; Finn, Peter R.
Abstract : Background: Low working memory (WM) capacity is associated with alcohol use disorders (AUDs). The importance of WM to adaptive functioning has led to a recent influx of studies attempting to improve individual WM capacity using various cognitive training methods. The present study aimed to examine the efficacy of complex WM training for improving WM capacity among individuals with AUD. Methods: Individuals were randomized to complete either adaptive WM training or active control training. We applied a methodologically rigorous and structured approach, including a battery of near and moderate transfer measures in those with AUDs and a control group. Additionally, we examined cognitive factors (at baseline) and other predictors of adherence, training task improvement, and transfer. Results: Results suggest improved WM in individuals with AUDs and controls, as evidenced by improved scores on several transfer measures, after adaptive WM training. However, individuals with AUDs showed poorer adherence and less improvement on the training tasks themselves. Neither IQ, WM, sex, nor condition predicted adherence. Level of training task performance, baseline WM, and IQ predicted transfer task improvement. Conclusions: This is the first study to rigorously examine both the efficacy of WM training in those with AUDs, and predictors of successful training program adherence and transfer in a large sample. Among study completers, results suggest that AUD status does not predict training improvement and transfer. However, AUD status did predict lower program adherence. WM training was more effective in those with higher cognitive ability at baseline. This study provides direct translation to the development of cognitive interventions for treating AUD. Abstract : The importance of working memory (WM) to adaptive functioning has led to an influx of studies attempting to improve WM in a variety of clinical populations. We examined the efficacy of a complex WM training program in those with Alcohol Use Disorders (AUDs), and predictors of effective training and adherence. AUD status predicted lower program adherence but not direct training effects for those who completed training, providing direct translation for the development of future cognitive interventions for AUDs.